Adolescent providers' knowledge of human papillomavirus vaccination age guidelines in five countries. Issue 7 (3rd August 2019) - Topazian, Hillary M.; Dizon, A. Mitch; Di Bona, Vito L.; Levitz, Lauren; Ramos, Silvina; Morgan, Karen; Kim, Chan Joo; Richter, Karin; De Sanjose, Silvia; Smith, Jennifer S.
ABSTRACT: Purpose : To examine provider knowledge of HPV vaccination age guidelines in five countries. Methods : A total of 151 providers of adolescent vaccinations in Argentina, Malaysia, South Africa, South Korea, and Spain were interviewed between October 2013 and April 2014. Univariate analyses compared providers' understanding of recommended age groups for HPV vaccination to that of each country's national guidelines. Results : In three of five countries surveyed, most providers (97% South Africa, 95% Argentina, 87% Malaysia) included all nationally recommended ages in their target age group. However, a relatively large proportion of vaccinators in some countries (83% Malaysia, 55% Argentina) believed that HPV vaccination was recommended for women above age 26, far exceeding national guidelines, and beyond the maximum recommended age in the United States. National median minimum and maximum age recommendations cited by the respondents for HPV vaccination were 11 and 29 years in Argentina (national guideline: 11–14), 13 and 48 years in Malaysia (guideline 13–14), 8 and 14 years in South Africa (guideline 9–14), 10 and 20 years in South Korea (guideline 11–14), and 11 and 12 years in Spain (guideline 11–14). In all countries, a higher percentage of vaccinators included all nationally recommended ages for vaccination, as compared to providers who did not administer HPV vaccination. Conclusions : Overall, a substantial proportion of providers incorrectly reported their country's age guidelines for HPV vaccination, particularly the upper age limit. As provider recommendation is among the strongest predictors of successful vaccination uptake among adolescents, improved education and clarification of national guidelines for providers administering HPV vaccination is essential to optimize prevention of infection and associated disease.